The Influential Relationship between Technical and Vocational Education and Training (TVET) and Employment Competence: A Study from Yunnan Province, China - Liu, Yisi; Salleh, Kahirol Mohd (Journal of Ecohumanism, 2024)
This study focuses on exploring the influential relationship between Technical and Vocational Education and Training (TVET) and the employment competence in Yunnan Province, China. Employment competence categorized into two main dimensions: the "hard" dimension consists of work stability and the ability to find a job (employability), and the "soft" level includes job satisfaction and salary level. In this study, 495 samples were collected through WenJuanXing using stratified random sampling method with professional stratification (Industrial Engineering, Agriculture, Tourist Industry, Health, and Internet Engineering). This study used survey questionnaire to collect data and quantitative research method to explore the relationship between TVET and the employment competence in Yunnan Province, China. The present study analyzed the relationship between TVET and employment competence through descriptive and inferential statistics. A survey of the employment status of 495 TVET graduates found that the Pearson's coefficients range from 0.367 to 0.470, indicating varying degrees of moderate to strong positive relationships between the TVET and employment competence in Yunnan Province, China, and in particular a high relationship with job satisfaction and salary levels. Such results bring recommendations for educational institutions in Yunnan Province China: the development of high-quality TVET program can enhance employment competence and thus reduce the unemployment rate at present.